Bibliographic Guide to the Two World Wars: An annotated survey of English-language Reference Materials by Gwyn M. Bayliss. - Claase, A.G. (Scientia Militaria - South African Journal of Military Studies, 2011)
An enormous quantity of material has been published on the First and Second World War. Dr Bayliss has compiled this bibliographic guide as an aid to researchers and has listed and critically discussed over 2 400 bibliographies and reference works to sources on this subject.